A proposed management model for the development of strategic information systems. (1st January 2000) - Pun, K.F.; Lee, M.K.O.
This paper discusses the development of strategic information systems (SIS) and examines the impact of SIS applications in operations management on sustaining organisational competitiveness. It reviews the methodology, the process and the critical parameters and factors of SIS development. A management model for SIS development that integrates various perspectives of competitive advantage, business strategy, information technology (IT) and information systems (IS) is proposed. The purposes of this paper are to review the state of published SIS research, and develop a management model that identifies a five-stage SIS development process. In synthesising SIS planning methodologies advocated in literature, the paper also elaborates an implementation guideline accompanying the proposed model.